(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
The clinical use of vitamins and anti-vitamins is central to the prevention, treatment, and biochemical mediation of disease in humans. Vitamins are micronutrients that play a role in a wide range of physiological functions, while anti-vitamins, whose role involves antagonizing the action of vitamins, have therapeutic uses in disease states resulting from hypervitaminosis and cancer. This review considers the medical use of each of the vitamins in clinical practice, the modes of action and uses of the anti-vitamins, and the therapeutic balance for safe treatment.